Reversible Corneal Toxicity of Retained Intracameral Perfluoro-n-octane - Alharbi, Saad S. (Middle East Afr J Ophthalmol, 2016)
A 58-year-old female presented with intracameral retained perfluoro-n-octane (PFO) following previous retinal reattachment surgery. After 4 years of follow-up without related sequelae, the patient complained of a gradual decrease in vision secondary to corneal edema with whitish corneal precipitate inferiorly corresponding to the area of retained PFO. Three weeks after anterior chamber washout, corneal edema resolved and the patient obtained 20/40 visual acuity. Even though PFO considered to have a relatively good safety profile, early anterior chamber washout may prevent corneal toxicity and avoid later persistent corneal decompensation.